DAMPAK MUTASI KEPALA SEKOLAH TERHADAP MANAJEMEN SEKOLAH ISLAM: STUDI KASUS - Umi Sarjiatun; Baidi Baidi (at-Tahsin, 2026)
This study aims to analyze the impact of principal rotation on strategic planning, human resource management, and teacher performance within the context of Islamic waqf educational foundations. Despite its potential for institutional growth, the rotation of school leadership often creates managerial instability and professional uncertainty that challenge the continuity of Islamic educational values. To address this, a qualitative approach with a multi-site case study design was employed. Data were rigorously collected through in-depth interviews, participant observations, and documentation studies to ensure a comprehensive understanding of the transition. The analysis followed a thematic technique integrated with source triangulation to validate the findings across different organizational levels. The results demonstrate that principal rotation serves as a significant catalyst for updating school visions to be more technologically adaptive while remaining rooted in Islamic principles. Furthermore, the transition led to a more efficient and competency-based restructuring of human resource management within the foundation. Teacher performance significantly improved through the implementation of transformational leadership styles that effectively integrated spiritual values into daily academic activities. The findings also reveal that the rotation fostered a renewed commitment to organizational transparency and professional accountability. Future research should investigate the long-term sustainability of these managerial transformations over an extended longitudinal period to assess their lasting impact on student outcomes.